Dual PI3K/mTOR inhibition shows antileukemic activity in MLL-rearranged acute myeloid leukemia - Sandhöfer, Nadine; Walter, Gina J.; Fröhling, Stefan (Leukemia, 2015)
In acute myeloid leukemia (AML), several signaling pathways such as the phosphatidylinositol-3-kinase/AKT and the mammalian target of rapamycin (PI3K/AKT/mTOR) pathway are deregulated and constitutively activated as a consequence of genetic and cytogenetic abnormalities. We tested the effectiveness of PI3K/AKT/mTOR-targeting therapies and tried to identify alterations that associate with treatment sensitivity. By analyzing primary samples and cell lines, we observed a wide range of cytotoxic activity for inhibition of AKT (MK-2206), mTORC1 (rapamycin) and PI3K/mTORC1/2 (BEZ-235) with a high sensitivity of cells carrying an MLL rearrangement. In vivo PI3K/mTOR inhibition delayed tumor progression, reduced tumor load and prolonged survival in an MLL-AF9+/FLT3-ITD+ xenograft mouse model. By performing targeted amplicon sequencing in 38 MLL-AF9+ and 125 cytogenetically normal AML patient samples, we found a high additional mutation rate for genes involved in growth factor signaling in 79% of all MLL-AF9+ samples, which could lead to a possible benefit of this cohort. PI3K/mTOR inhibition for 24 h led to the cross-activation of the ERK pathway. Further in vitro studies combining PI3K/mTOR and ERK pathway inhibition revealed highly synergistic effects in apoptosis assays. Our data implicate a possible therapeutic benefit of PI3K/mTOR inhibition in the MLL-mutated subgroup. Inhibiting rescue pathways could improve the therapeutic efficacy of PI3K-targeted therapies in AML.